2011
DOI: 10.1007/s00018-010-0618-x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the Klf4 DNA-binding domain links to self-renewal and macrophage differentiation

Abstract: Krueppel-like factor 4 (Klf4) belongs to the Sp/Klf family of zinc-finger transcription factors and is indispensable for terminal maturation of epithelial tissues. Furthermore, it is part of a small set of proteins that are used to generate pluripotent embryonic stem cells from differentiated tissues. Herein, we describe that a Klf4 zinc-finger domain mutant induces self-renewal and block of maturation, while wild-type Klf4 induces terminal macrophage differentiation. Moreover, we present the crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 44 publications
6
90
0
1
Order By: Relevance
“…Previous studies showed that the second zinc finger recognizes the GTG or GCG triplet in the corebinding site, whereas the third zinc finger plays an important role in overall binding site preferences (56,57). Among the KLFs analyzed in this study, the third zinc finger shows the greatest variation in amino acid sequence.…”
Section: Regulation Of Epha5 Expression By Klfs and Dna Methylation-tmentioning
confidence: 71%
“…Previous studies showed that the second zinc finger recognizes the GTG or GCG triplet in the corebinding site, whereas the third zinc finger plays an important role in overall binding site preferences (56,57). Among the KLFs analyzed in this study, the third zinc finger shows the greatest variation in amino acid sequence.…”
Section: Regulation Of Epha5 Expression By Klfs and Dna Methylation-tmentioning
confidence: 71%
“…The defining feature of KLFs is the presence of a conserved, tandem repeat of three Cys 2 -His 2 -type zinc fingers at their C termini, through which KLFs make sequence-specific contacts with GC-rich and CACCC-related elements of DNA (3)(4)(5)(6). While as a whole this domain is highly conserved within the family, specific amino acid differences between the various KLFs result in different DNA-binding preferences (7). As such, individual KLFs have been shown to regulate overlapping, but also distinct, sets of target genes (8,9).…”
mentioning
confidence: 99%
“…The zinc finger binds to a DNA triplet (blue) through -1, +3 and +6 amino acid residues (yellow) of the finger (relative to the start of the α-helix). Figure was generated with Cn3D (NCBI) from the structure of KLF4 (zf2) bound to DNA; PBD ID 2WBU (Schuetz et al, 2011).…”
Section: Common Structures Of Klfsmentioning
confidence: 99%
“…2WBU) (Schuetz et al, 2011) was used to interpret KLF1-DNA interaction, as DNA-contacting residues from ZF2 of KLF4 and KLF1 are identical. The Nan-KLF1 and CDA-KLF1 mutant conformations was modelled by substituting E339 for D and K, respectively, with the sidechain conformation chosen from a backbone-dependent rotamer library (Dunbrack & Karplus, 1993).…”
Section: Structural Predictionsmentioning
confidence: 99%
See 1 more Smart Citation